Effect of tear osmolarity on postoperative refractive error after cataract surgery (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To analyze the effects of tear osmolarity on postoperative refractive error and patient satisfaction after cataract surgery.Methods: The patients were divided into two groups based on the tear osmolarity (group Nr 1-normal tear osmolarity, 310 mOsm/L). Preoperative and postoperative (1 month after surgery) visual acuities (VAs), refractions, and best corrected VAs (BCVAs) were measured. The postoperative refractive error was measured as the spherical equivalent (SE) (SE = sphere + [0.5 × cylinder]). The postoperative VA, BCVA, and SE were compared between groups.Results: Eighty-one patients were included in the study (group Nr 1=40 patients and group Nr 2=41 patients). The hyperosmolar group had a statistically significant higher postoperative refractive error (p
Keywords: tear osmolarity; dry eye disease; cataract surgery; refractive error